Unaddressed tax disputes: the case of South Sudan's dysfunctional Tax Appeals Board and lessons from Uganda and South Africa - Anei, Joseph Majak Madut (Department of Commercial Law, 2023)
This research will explore the tax disputes resolution mechanisms by the Tax Appeals Board and High Court under the Taxation Act, 2009 in the Republic of South Sudan. Additionally, it will examine legislative gaps affecting the independence and competence of Tax Appeals Board in its mandate of resolving tax disputes within the tax administration system. In addition, the study will explore the review process of Tax Appeals Board's decisions by the High Court of South Sudan. By contrast, however, this research will further examine the tax disputes resolution mechanisms in Uganda and South Africa with the focus on the legislative guarantees on the independence and competence of the statutory bodies tasked with tax disputes resolution. This research is segmented into six chapters: Chapter One looks at the introductory background of the research while Chapter Two deals with functional framework of Directorate of Taxation, Tax Appeals Board, rights and duties of a taxpayer. Chapter Three which is the crux of this research deals with issues of independence and competence of the Tax Appeals Board as well as appeals to High Court. Chapters Four and Five look at tax dispute resolution mechanisms in Uganda and South Africa respectively. Finally, Chapter Six wraps up this research with findings and recommendations.